2001
DOI: 10.1148/radiol.2202010063
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Lesions: Characterization with Diffusion-weighted Echo-planar MR Imaging

Abstract: Measurement of ADCs may be used to characterize head and neck lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
420
8
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(459 citation statements)
references
References 23 publications
23
420
8
8
Order By: Relevance
“…The b value of 500 s/mm 2 was used in our study to acquire DW-MR images with sufficient diffusion weighting and image quality. The b values used by other investigators (24,25,27,45) were in the range of 128*1000 s/mm 2 . From a clinical perspective, this pilot study suggests that DW-MRI could have clinical relevance in providing additional risk stratification information for small thyroid cancers that appear to be confined to the thyroid based on standard preoperative ultrasound and clinical evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The b value of 500 s/mm 2 was used in our study to acquire DW-MR images with sufficient diffusion weighting and image quality. The b values used by other investigators (24,25,27,45) were in the range of 128*1000 s/mm 2 . From a clinical perspective, this pilot study suggests that DW-MRI could have clinical relevance in providing additional risk stratification information for small thyroid cancers that appear to be confined to the thyroid based on standard preoperative ultrasound and clinical evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported the ability of DWI to discriminate between different histological lymph node cancers in the neck [28][29][30]. Others showed that ADC determination on DWI-MRI may have added value in discriminating malignant from benign lymph nodes in the neck [19,20,27]. All studies were performed in patients with palpable cervical lymphadenopathy (clinical positive necks), and further evaluation by MRI was limited to selected enlarged lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DWI provides in characterization of different tissues and lesions. Previous reports showed the utility of DWI in the region of the head and neck for different pathology [19][20][21][22][23][24][25][26]. In studies focused on nodal staging, the imaging results were based on series with only clinical positive necks in which large lymph nodes were selected for evaluation [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding primary tumors, it has been clearly demonstrated that malignant lymphoma has the lowest ADC values followed by carcinoma, benign tumor, and cystic lesions, and that ADC values significantly differ between well-differentiated and poorly differentiated lesions [46,47]. ADC significantly correlates with cellularity, stromal component, and nuclear-cytoplasmic ratio; and the positive correlation of ADC and stromal component may partly reflect the poor prognostic value of high pre-treatment ADC [48].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%
“…The advantages of suppressing the signal from fat is to suppress artifacts due to high fat signals, to improve T2 contrast between fatty and non-fatty tissue, to enable detection of enhancing tumors hidden in fatty tissue, and the proof of adipose tissue, such as in lipoma, or cholesterol granuloma. Reading T1w and T2w basic sequences and T2w fat sat images is important because the very high STIR/TIRM ▶ Table 1 (Continuation) MRI sequences main pathologies/field of application diagnostic clues paraganglioma high peak enhancement, SER, and short TME on DCE [37] schwannoma low peak enhancement and SER with a longer TME on DCE [37] diffusionweighted imaging primary tumors low ADC values (lymphoma, followed by carcinoma, benign tumor and cystic lesions) [47] lymph node staging low ADC values [49] residual cancer after chemoradiation therapy lower increase in the percentage change of the mean ADC or decrease in ADC during treatment [51,52] cholesteatoma high signal on DWI [60] Granulation tissue, fibrous tissue, cholesterol granuloma or serous fluid…”
Section: Introductionmentioning
confidence: 99%